Further chemical constituents of Scoparia dulcis L. (Scrophulariaceae) originating in Vietnam - Giang, Phan Minh; Huynh Nga, Dang Thi; Hai, Nguyen Xuan; Son, Phan Tong (Vietnam Journal of Chemistry, 2014)
Palmitic acid (1), b-sitosterol (2), glutinol (3), and a mixture of b-amyrin (4) and isomultiflorenol (5), whose structures were determined by using spectroscopic methods, were isolated from the aerial parts of Scoparia dulcis L. (Scrophulariaceae). The volatile fraction of S. dulcis was analyzed by GC-MS to show the accumulation of methyl esters of fatty acids. The useful compound methoxybenzoxazolinone (MBOA) was found to be localized in the CH2Cl2-soluble fraction of the MeOH extract. For the direct qualitative and quantitative evaluation of MBOA in the CH2Cl2-soluble fraction 1H-NMR method was applied in this study. Antimicrobial test of the soluble fractions and MBOA showed inhibition on Escherichia coli, Pseudomonas aeruginosa, and Saccharomyces cerevisiae. Keywords: Scoparia dulcis; Scrophulariaceae; triterpenoid; methoxybenzoxazolinone (MBOA)